Numerical simulation research on damage characteristics and acoustic emission response of coal with pre-existed cracks - CHEN Pan; LI Dexing (Gong-kuang zidonghua, 2018)
In order to research influences of crack inclination angle on damage characteristics and acoustic emission characteristics of coal, numerical simulation of coal with pre-existed cracks of different inclination angles under uniaxial compression was conducted using RFPA2D numerical simulation software, and crack propagation mode, mechanical properties and acoustic emission response influenced by crack angel were analyzed. The analysis results show that the main fracture extends in the direction perpendicular to the middle of the pre-existed crack when pre-existed crack angle (α) is 0°. For specimens with α of 15,30,45,60,75°, the main crack propagation mode are typical wing crack, or Y-shaped crack propagation mode developed from wing crack. However, there is randomness in the distribution of the main cracks of the specimen with crack angel of 90° and the intact specimen. The existence of cracks reduces the peak strength and modulus of elasticity of the coal, and the peak strength and modulus of elasticity both increase with pre-existed crack angel, the former increases with the relation of quadratic function, and the latter increases as inclined 'S'. In addition, with the increase of the inclination angle, the specimens gradually transform from ductile failure to brittle fracture. When main fracture occurs the instantaneous acoustic emission count has a periodic increase, namely the instantaneous acoustic emission count increases in turn at three stages when α is 0-45, 60-75, 90° and the intact specimen.